Learning Flow in Café: The Role of Spatial Characteristics - Amanda Magdareta Rompas; Hanson E. Kusuma; Cynthia E. V. Wuisang (DIMENSI: Journal of Architecture and Built Environment, 2025)
Cafés have often been used as informal learning spaces by Indonesian college students in recent years. However, as a public space, cafes are considered by several people as not suitable for learning activities that require a high level of concentration. This research aims to identify café spatial characteristics that can affect learning activities and students’ flow experience. Flow, as defined by Csikszentmihalyi (1990), refers to a state in which individuals engage in an activity with deep concentration, a sense of control, and intrinsic enjoyment, often accompanied by a loss of time awareness. The relationship between the state of flow and learning activities is also explored. The research uses a mixed-method approach. In the first stage, an exploratory qualitative study was conducted to indentify key spatial factors and patterns of student learning in cafés. In the second stage, an explanatory quantitative study was carried out, using closed-endded questions derived from the qualitative findings to test the realtionships between spatial characteristics, flow dimensions, and learning activities through factor analysis, regression, and correlation analysis.   The analysis results show enjoyment as the dimension of flow experience students tend to encounter when studying in cafes. The findings implied that café spatial characteristics must stimulate positive emotions, prevent visual and audial distractions, and promote social interactions between learners to boost flow and smooth the learning activities.